The Antelope Uranium Project A Comparison Of ISR And Heap Leach Extraction - D Beahm (Society for Mining, Metallurgy & Exploration, 2007)
Introduction The Energy Metals Corporation (EMC) holds numerous mineral properties in the northern portion of the Great Divide Basin including the JAB Property, one of several potential properties being planned for development as a satellite facility to the greater Antelope Uranium Project. A National Instrument 43-101 Technical Report has been completed for the JAB property. This report estimates total measured and indicated mineral resources on the property totaling 3,555,022 pounds U3O8 contained in 2,400,875 tons at an average grade of 0.073 % U3O8 at a .25 GT cutoff in accordance with CIM Standards on Mineral Resources and Reserves. The JAB Property is located in Sections 13, 14, 15, 16, 21, 22, and 23, Township 26 North, Range 94 West, approximately Latitude 42o 14’ North and Longitude 108o 00’ West (Figure 1, Location Map). This property consists of unpatented mining lode claims and Wyoming State mineral leases comprising approximately 2,100 acres.